IN SITE LEARNING: INVENTARISASI PERMASALAHAN PETANI KARET - Sulistyowati, H.; Ruliyansyah, A.; Pramulya, M. (Buletin Udayana Mengabdi; Vol 23 No 4 (2024): Buletin Udayana Mengabdi, 2023)
Kelam Permai sub-district is located in Sintang Regency where the number of rubber farmers has increased by 39% in the period 2015 – 2020. The common problem faced by rubber farmers in Kecamatan Kelam Permai is low dry-rubber productivity (0.7 tons/ha) which occurs due to farmers’ inadequacy of implementing good agricultural practices in their farming, unable to identify and inventory the problems they experience. It is considered necessary to provide the farmers counseling on proper rubber cultivation techniques, followed by co-learning efforts in identifying and inventorying the problems. The results showed that after participating in counseling, rubber farmers gain knowledge and understand the importance of implementing good agricultural practices in their farming. Identifying problems efforts were successfully carried out, followed by inventorying of problems, namely: farmers have not practice good agricultural practices, rubber plants suffer Pestalotiopsis, expensive fertilizers, and low latex selling price. It is suggested that rubber farmers should implement good agricultural practices in their farming to improve their latex productivity, propagate knowledges gained from PKM activities to other farmers whom do not participate in this activity, join farmer groups to establish communication with the government and related agencies in an effort to find solutions to existing problems. Keywords: counseling, low productivity, rubber